Change of Fatty Acids Compositions (Omega 3, 6, 9) from Milkfish (Chanos chanos Forsk) Bekasam Fermented with Different Carbohydrates Sources - Saga Gerlaping Negari; Eko Nurcahya Dewi; Laras Rianingsih (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2018)
Bekasam is one of fermentation products made from Milkfish (Chanos chanos Forsk). The aim of this study was to determine the effect of different sources of carbohydrates on fermented waste to fatty acid composition. The method used was experimental laboratories using Completely Randomized Design. The treatment applied was the use of different carbohydrate sources of rice, brown sugar and garlic in the milkfish bekasam production using 3 repetitions. The data were analyzed using Analysis of Variance and continued by Honestly Significant Difference test if there was any effect on the treatment given. The results showed that the difference of carbohydrate sources during fermentation process could affect the composition of fatty acids. Lactic acid bacteria use carbohydrate sources as energy to grow and then hydrolyze fat into fatty acids. The best result was bekasam with the sources of carbohydrate of rice with total value of Lactic Acid Bacteria 7,888 log cfu/g, Total Volatile Base Nitrogen value 34,796 mgN/100ml, lipid content 0,055% and the highest fatty acids compositions. The results of the study showed that the use of different sources of carbohydrate on bekasam had significant effect (P<5%) on the fatty acid composition on bekasam.